Daño oxidante en testículo de ratas lactantes desnutridas - Rosas Trejo, María de los Ángeles (Universidad Autónoma Metropolitana, 2017)
Children malnutrition is considered a severe public health problem, so much so that in 1956 the first classification was created to establish the different degrees of malnutrition. In the 1960s, studies were begun on the antioxidant defense systems and the concentration of micronutrients in malnourished children at a systemic level and their relation to the functional damage observed. The objective of the present investigation was to determine if malnutrition in lactating rats is related to an increase in oxidative damage in proteins and lipids due to the decrease in the expression and activity of enzymes with antioxidant function in the testicle, which would cause morphological changes to level of the seminiferous tubule inducing the possible alteration in the function of this organ. Experimental malnutrition was induced by the food competition method and the classification of rats with different degrees of malnutrition was performed at 21 days of age. The results obtained were quite revealing, since it was found a decrease in the expression and activity of enzymes with an antioxidant function such as SOD CuZn and CAT, but in the case of the GPx enzyme it showed a decreased expression and an elevated activity indicating that the testicle try in some way to balance the production of ROS. However, this was not enough to decrease the oxidative damage in lipids and proteins, a damage that was reflected in the morphology of the seminiferous tubule, a functional unit of the testicle, since a decrease in the total area of the tubule was observed, from the stage of MN1. Despite the variety of studies conducted on malnutrition, this research reports its effect on the testicle for the first time. The results of the antioxidant defense system showed that malnutrition is associated with a decrease in the expression and activity of enzymes with antioxidant function that causes damage to biomolecules, which correlates with the reduction of the total area of the seminiferous tubule. Finally it is important to point out that malnutrition had a strong impact on all parameters analyzed from MN1, not finding a differential effect between MN1, MN2 and MN3 during lactation.; La desnutrición en niños se considera un grave problema de salud pública, tanto que, en 1956 se creó la primera clasificación para establecer los diferentes grados de desnutrición. En los años 60´s se comenzaron a realizar estudios sobre los sistemas de defensa antioxidante y la concentración de micronutrientes en niños desnutridos a nivel sistémico y su relación con los daños funcionales observados. El objetivo de la presente investigación fue determinar si la desnutrición en ratas lactantes se relaciona con un aumento en el daño oxidante en proteínas y lípidos y a una disminución en la expresión y actividad de enzimas con función antioxidante en testículo, lo cual provocaría cambios morfológicos a nivel del túbulo seminífero, induciendo la posible alteración en la función de este órgano. La desnutrición experimental se indujo mediante el método de competencia de alimento y la clasificación de las ratas con diferentes grados de desnutrición se realizó a los 21 días de edad. Los resultados obtenidos fueron bastante reveladores, ya que se encontró una disminución en la expresión y actividad de enzimas con función antioxidante como SOD CuZn y CAT, pero en el caso de la enzima GPx ésta presentó una expresión disminuida y una actividad elevada indicando que el testículo trata de alguna manera de equilibrar la producción de ERO. Sin embargo, este no fue suficiente para disminuir el daño oxidante en lípidos y proteínas, daño que se vio reflejado en la morfología del túbulo seminífero, unidad funcional del testículo, ya que se observó una disminución del área total del túbulo, desde la etapa de DN1. A pesar de la variedad de estudios realizados sobre la desnutrición, en esta investigación se reporta por primera vez su efecto sobre el testículo. Los resultados del sistema de defensa antioxidante mostraron que la desnutrición está asociada con disminución en la expresión y actividad de enzimas con función antioxidante que provoca daño a biomoléculas, lo que se correlaciona con la reducción del área total del túbulo seminífero. Finalmente es importante señalar que la desnutrición tuvo un fuerte impacto en todos los parámetros analizados desde la DN1, no encontrando un efecto diferencial entre la DN1, DN2 y DN3 durante la lactancia.